Teknologi Pengolahan Dan Pemasaran Olahan Kopi Perluasan Pasar Nasional Dan Global Unggulan Kabupaten Tuban - Widiana, Muslichah Erma; Suyanto, Suyanto; Arizal, Arif; Ananda Kurniawan, Bagus; Ray Prayoga, Rafael (Seminar Nasional Manajemen, 2025)
One of the industrial sectors that serves as the main pillar of the economy in Tuban Regency is the coffee industry. Apparently, this has become one of Tuban’s identities, known as an industrial area. Drinking coffee has now become a lifestyle for millennial children and is no longer just a drink to ward off drowsiness. This is reflected in the proliferation of cafes or shops selling brewed coffee drinks throughout the archipelago. Now, to enjoy quality coffee, you no longer have to go to Starbucks or Coffee Bean. Local coffee shops have now appeared everywhere, from the streets, business districts, to malls (Ministry of Agriculture, 2017). One of the coffee industries in Tuban, PT. Aisindo Karya Mandiri, led by Mr. Agus, faces several challenges: 1) the grinding of coffee beans into powder is mixed with air, resulting in suboptimal coffee powder yield as much is wasted along with the air expelled from the machine, 2) the production site has high pollution levels, 3) business management is not optimal due to the implementation of job desks, 4) workers from the surrounding community have low commitment and work ethic. Objectives: through the PM-UPUD program for PT. Aisindo Karya Mandiri from Pakel-Montong Village, Tuban, East Java: 1) Improve the efficiency of the coffee bean grinding process through modification or innovation of tools to minimize product loss (coffee powder carried away by wind) and enhance the quality and quantity of production. 2) Reduce pollution levels at the production site and implement environmentally friendly Occupational Safety and Health (OSH) principles. 3) Improve business management through training in business management systems and clearer, more professional job desk assignments to increase work productivity. 4) Enhance the capacity and work ethic of local workers by providing soft skills training, work motivation, and understanding the importance of responsibility and contribution in the joint effort. Method: 1) Socialization and coordination of the service team and PT. Aisindo Karya Mandiri partners. 2) Training: a) tool innovation to minimize coffee powder loss, b) tools to reduce pollution levels, c) business management system and clear and professional job desk distribution, d) soft skills, work motivation, and understanding the importance of responsibility and contribution in joint efforts. 3) Technology implementation. 4) Mentoring and evaluation. 5) Program sustainability. Results and Conclusions: 1) Silo machine with blower (Silo: H. 120cm and D. 30cm, Plate 1mm, Frame ump 50 P.L.T adjusted), (blower: Diameter 40cm Thickness 15cm, Plate thickness 1.2mm). 2) Exhaust fan (Specifications: FBD-800, 32inc/800mm, Speed 450RPM, Air Flow 18000CMH, Power 370watt). 3) Improvement in Partner Managerial Capacity. 4) Positive Changes in Work Ethos and Commitment.